Al-Miqyās al Islāmī wa al-hal al-amthal lil qadāyā al-ijmāiyaah - Amroh Muhammad Qosim (Al-Jami'ah: Journal of Islamic Studies, 2002)
Problems that happened and developed in society could not be separated from human beings as the main doer. Human beings have many characteristics that contribute to its attitude in society. Two of its characteristics, and also its major Powers are its curiosity and its need of financial. However human beings would not achieve its highest curiosity unless he/she already has been fulfilled its financial need. So, the two characteristics is rather a cause-effect relationship than a complementarily relationship. These two characteristics, however, are significant to analyze some social problems. One of the problems in society is that there are a small number of rich people and the existence of an enormous quantity of the poor people. The writer assumes that the above economical gap is initiated by an unjust social order. With her framework of Islam, the writer would portray some social problems and then provide some solutions for the problems. For the writer, human beings should put everything, as it should be and as it stated in Islam, because Islam has already made an obvious pattern to reach the ultimate goal of life.[Berbagai persoalan yang muncul dan berkembang dalam masyarakat tidak bisa dilepaskan dari manusia sebagai pelaku utama. Manusia memiliki berbagai karakteristik yang menentukan sikapnya dalam bermasyarakat. Dua di antara karakteristik dan sekaligus potensi menonjol manusia adalah rasa ingin tahu dan kebutuhan akan materi. Walaupun demikian, yang disebut pertama tidak bisa optimal sebelum faktor kedua terpenuhi. Jadi, dua karakteristik itu lebih bersifat sebab-akibat dari pada bersifat komplementer. Dua karakteristik ini cukup penting untuk melihat berbagai permasalahan yang muncul di masyarakat. Di antara permasalahan yang cukup signifikan adalah adanya orang kelompok kecil masyarakat yang kaya, di satu pihak, dan kelompok besar masyarakat yang tidak mampu di pihak lain. Penulis beranggapan bahwa kesenjangan ekonomi di atas bermula dari tatanan sosial yang serba tidak adil. Dengan kacamata Islam, penulis akan memotret berbagai persoalan sosial dan kemudian menyodorkan altematif solusi. Bagi penulis, manusia harus meletakkan berbagai persoalan sesuai dengan proporsinya dalam agama Islam, karena Islam telah membuat standar yang jelas untuk mencapai tujuan hidup yang ideal.]